Celtis neglecta (Cannabaceae), a new species from Zhejiang, eastern China - Chen, Zi-Lin; Lu, Yi-Fei; Zhang, Wei-Bin; Xu, Xiao-Feng; Wang, Pan; Jin, Xiao-Feng (Phytotaxa, 2017)
Celtis neglecta Zi L. Chen & X. F. Jin, a new species from Zhejiang, China, is described and illustrated. This new species is most similar to Celtis julianae C. K. Schneid. and C. vandervoetiana C. K. Schneid. It differs from Celtis julianae in having young shoots, petioles, and both mid-ribs and lateral veins of the lower leaf surfaces densely whitish pubescent, and fruit pedicels glabrous or sparsely whitish pubescent. It differs from Celtis vandervoetiana in having young shoots and petioles densely whitish pubescent, and being sparsely whitish pubescent on the upper leaf surfaces, and densely whitish pubescent on both mid-ribs and lateral veins of the lower leaf surfaces. Sequences of the plastid intergenic spacer regions atpB-rbcL and trnL-trnF demonstrate that Celtis julianae and C. vandervoetiana are the closest extant relatives of this new species.